Procedures for Integrating, Testing and Operating Advanced Microsatellites - Miranda, Ricardo Kehrle; da Costa, João Paulo C.L.; Eishima, Takashi; Nakamura, Yuya; Galdo, Giovanni Del; Roemer, Florian; Ribeiro, Lucas D.X. (IFAC-PapersOnLine, 2016)
The costs involved in building and launching standard big satellites are very high. Due to the miniaturization of electronic and mechanical devices, smaller and cheaper satellites, also known as microsatellites, are becoming more capable, and thus, more important in space exploration. In other words, microsatellites can unite simplicity with capacity to carry more sophisticated payloads. This paper details practical aspects of microsatellites ranging from integrating process, vibration tests and vacuum chamber tests to its operation.
CRIS-Team Scopus Importer:2025-11-10
Keywords: command; environmental tests; integration; satellites; telemetry